THE EFFECT OF MASASE COUNTERPRESSURE ON LABOR PAIN KALA ONE ACTIVE PHASE IN MOTHER BIRDS IN BPM SETIA - Hadriani, Hadriani; Purwaningsih, Eka (Tadulako University, 2018)
Background & Objective: Labor pain can cause stress which can cause excessive hormone release such as ketocolamine and steroids. Pain can be reduced by pharmacological techniques and non-pharmacological techniques. Pharmacological techniques using analgesic drugs, while non-pharmacological techniques are pain control by using counterpressure techniques that reduce pain sensations by inhibiting pain from the source. The purpose of this study was to determine the effect of counterpressure massage on labor pain kala one active phase in maternity at BPM Setia. Material and Method : This research is Quasi Experimental with one group pretest and posttest design with a population of all mothers giving birth during the active phase at Setia BPM and a sample of 15 respondents. Data analysis using the Wilcoxon Signed Rank Test. Results: The scale of pain before counterpressure massage was performed in the first phase of active maternity, 9 respondents (60.0%) experienced severe pain, moderate pain as many as 3 respondents (20%) and very severe pain 3 respondents (20%). The scale of pain after counterpressure massage, mild pain 2 respondents (13.3%), moderate pain 9 respondents (60.0%) and experiencing severe pain 4 respondents (26.7%). The bivariate analysis showed p-value = 0,000. Conclusion: The conclusion of this study was that there were significant differences in pain before and after counterpressure massage in the first maternal phase of active at Setia BPM. Suggestions for midwives to be able to apply counterpressure massage techniques to reduce labor pain when I am the active phase of maternity.